Tax Awareness, Tax Sanctions, and Tax Evasion: The Role of Tax System Moderation in Indonesia - Tandry Whittleliang Hakki; Jobrinson Simanungkalit; Merna Surjadi; Marshia Loanza (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
The Ministry of Tourism and Creative Economy has set a target to mentor 100 startups through the IndoBisa 2024 program. Young entrepreneurs in the early stages of their businesses need tax education to become compliant taxpayers and avoid engaging in tax evasion. This study aims to analyze the influence of Tax Awareness and Tax Sanctions on young entrepreneurs' intention to evade taxes, as well as to examine the moderating role of the Taxation System. A quantitative approach was employed using primary data collected from members of HIPMI in Jakarta and East Java. The sampling technique used was purposive sampling. Hypotheses were tested using multiple linear regression analysis with the help of SPSS. The results show that: (1) Tax Awareness does not have a significant effect on tax evasion intention; (2) Tax Sanctions have a positive and significant effect on tax evasion intention; (3) the Taxation System does not moderate the relationship between Tax Awareness and tax evasion intention; and (4) the Taxation System strengthens the influence of Tax Sanctions on tax evasion intention.